Association of HLA‐DQB1*03:01 and DRB1*11:01 with spontaneous clearance of hepatitis C virus in Chinese Li ethnicity, an ethnic group genetically distinct from Chinese Han ethnicity and infected with unique HCV subtype. Issue 10 (5th July 2019) - Huang, Jieting; Xu, Ru; Wang, Min; Liao, Qiao; Huang, Ke; Shan, Zhengang; You, Qingzhu; Li, Chengyao; Rong, Xia; Fu, Yongshui
Abstract: Specific human leukocyte antigen (HLA) class I and class II alleles have been associated with spontaneous clearance or persistent infection of hepatitis C virus (HCV), which seemed to be restricted by the host's ethnicity and viral genotype. Recently we reported a high prevalence and spontaneous clearance rate of HCV in a cohort of Chinese Li ethnicity who were infected with new variants of HCV genotype 6. In this study, we found that the distribution of HLA class I and class II alleles in HCV infected individuals of Chinese Li ethnicity (n = 143) was distinct from that of Chinese Han ethnicity which was reported in our previous study. HLA‐DRB1*11:01 and DQB1*03:01 were more prevalent in Chinese Li subjects who cleared HCV spontaneously than those who were chronically infected ( P = .036 and P = .024, respectively), which were consistent with our previous report regarding the Chinese Han population. Multivariate logistic regression analysis showed that DQB1*03:01 (odds ratio = 3.899, P = .017), but not DRB1*11:01, associated with HCV spontaneous clearance, independent of age, sex, and IFNL3 genotype. Because DQB1*03:01 and DRB1*11:01 were tightly linked because of linkage disequilibrium, our results clearly supported the associations of these two alleles with HCV spontaneous clearance in Chinese Li as well as Han ethnicity.